Risk Factors Associated With Prolonged Antibiotic Use in Pediatric Bacterial Meningitis - He, Cuiyao; Hu, Xiaogang; Li, Tingsong; Wu, Qing; Fan, Jisan; Zhou, Yan; Jiang, Li; Hong, Siqi; Luo, Yuanyuan (Frontiers in Pharmacology, 2022)
Objectives: To determine the risk factors associated with a prolonged antibiotic course for community-acquired bacterial meningitis (BM) in children. Methods: This retrospective cohort study included children aged 1 month to 18 years with community-acquired BM due to a confirmed causative pathogen from 2011 to 2021. Patients were divided into an antibiotic prolongation group and a nonprolongation group according to whether the antibiotic course exceeded 2 weeks of the recommended course for the causative pathogen. Associations of important clinical characteristics and laboratory and other parameters with antibiotic prolongation were assessed using univariate and multivariable regression logistic analyses. Results: In total, 107 patients were included in this study. Augmented renal clearance (ARC) (OR, 258.531; 95% CI, 15.492-4314.476; P<0.001) was associated with a prolonged antibiotic course; however, septic shock, causative pathogen, preadmission antibiotic use, peripheral white blood cell (WBC) count, initial cerebrospinal fluid (CSF) WBC count, CSF glucose, CSF protein, and surgical history were not associated with the prolonged antibiotic course. Patients with ARC had more total fever days (median time: 14 days vs. 7.5 days), longer hospitalization (median time: 39 days vs. 24 days), higher rates of complications (72.34% vs. 50%) and antibiotic adjustments (78.723% vs. 56.667%) than patients with normal renal function. Conclusion: ARC is an independent risk factor for prolonged antibiotic use in children with community-acquired BM. ARC may be associated with longer fever and hospitalization durations, higher rates of complications and antibiotic adjustments.